Pengaruh Keragaman Produk, Harga, Dan Lokasi Terhadap Minat Beli Di Pasar Tempurejo Kresek Kota Kediri - Geya Fajar Agustina; Moch. Saleh Udin; Taufik Akbar (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This research aims to explain and prove the hypothesis regarding whether there is an influence of product diversity, price and location on purchasing interest at the Tempurejo Kresek market, Kediri City. This research uses descriptive research with quantitative methods with a sampling technique, namely non-probability sampling with an accidental sampling method with a population of 210 consumers and a sample size of 138 respondents. The analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression test, t test (partial), F test (simultaneous) and coefficient of determination (R2) which were processed using the SPSS version 25 program. The research results obtained are: states that product diversity partially has a positive and significant effect on purchase intention, obtaining a significant t value of 0.012 <0.05. Price partially has a positive and significant effect on buying interest, obtaining a significant t value of 0.000 < 0.05. Location partially has a positive and significant effect on buying interest, with a significant t value of 0.026 <0.05. Product diversity, price and location simultaneously have a positive and significant effect on buying interest in the Tempurejo Kresek market, Kediri City, looking at the significant F value of 0.000 < 0.05.